PERAN KAUM MUDA DESA LABANG DALAM UPAYA PELESTARIAN BUDAYA SUKU DAYAK KEBAHAN DALAM PERSPEKTIF EVRING GOFFMAN - Julio purba kencana; Yohanes I Wayan Marianta (Jurnal Budaya Nusantara, 2023)
The focus of this study is the role of the youth of Labang village in efforts to preserve the culture of the Kebahan Dayak people from the perspective of Evring Goffman. Today, the attention of young people to efforts to preserve culture is very apprehensive. Many of them prefer to follow current trends rather than participate in preserving the culture that is their identity. This situation makes the cultures of every tribe in the country of Indonesia slowly become extinct. However, not all young people have forgotten their role in preserving the culture of their tribe. One example is the young people of the Kebahan Dayak tribe in the village of Labang, West Kalimantan. As young people of the Dayak Kebahan tribe they are called to take part in cultural preservation. The method used in this study is library research. Meanwhile, the methodology used in this study is a critical reflection on the role of young people of the Kebahan Dayak tribe in efforts to preserve culture within the framework of Evring Goffman's dramaturgy. By looking at the human process in taking its role in life according to the dramaturgical lens of Evring Goffman. we can understand and correctly understand our duties as human beings in the world.